The use of underground storage organs in the Early Neolithic (Linearbandkeramik and Blicquy/Villeneuve-Saint-Germain) in the Paris Basin: the contribution of starch grain analyses - Clarissa Cagnato; Caroline Hamon; Aurélie Salavert; Michelle Elliott (Revue d'ethnoécologie)
Underground storage organs are poorly preserved in the archaeological record, and as a result their contribution to the diet of ancient societies is poorly understood. Starch grain analysis is a well-established methodology used in archaeology to reveal the use of various plants, including tubers, rhizomes, and roots. This paper presents the results of a study of starch grains recovered from millstones from various archaeological sites located in the Paris Basin. Our results highlight the use of tubers by these first agricultural populations at the beginning of the Neolithic (Linearbandkeramik and Blicquy-Villeneuve-Saint-Germain; 5200-4700 BC), providing new data on their contribution to the diet of agro-pastoral societies.